BALIQ VA BALIQ MAHSULOTLARIDAN ORTTIRILISHI MUMKIN BО‘LGAN AYRIM KASALLIKLAR - Ishmo‘minov B.B., Ishmo‘minov B.B. (Actual problems and prospects of the study of the fauna, 2024)
A process of preparing of the fish foods by using of salt, steam and heat is not used widely. Because, a taste of fish will be kept in the meal, many people do not even approximate that they have been infected. Signs of illness are allergic or like gastro intestinal tract and liver.